2014
DOI: 10.5539/gjhs.v6n4p285
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health Inequalities in Iran: A Focus on the Distribution of Health Care Facilities

Abstract: Background and objective:Equality in distribution of health care facilities is the main cause for access and enjoyment to the health. The aim of this study was to examine the regional disparities in health care facilities across the Markazi province.Methods:This was a cross-sectional study. Study sample included the cities of Markazi province, ranked based on 15 health indices. Data was collected by a data collection form made by the researcher using statistical yearbook. The indices were weighted using Shanno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
(11 reference statements)
1
23
1
1
Order By: Relevance
“…The results showed that the prevalence of each type of malnutrition, in terms of wasting, stunting and underweight were 7.8, 12.4 and 10.5 percent, respectively. One reason for the rather high overall prevalence of all three indicators in this review is that the majority of studies were conducted in the cities or provinces in which socioeconomic status was middle or low and we know that health and economic differences across Iranian provinces are very wide (22,23). The household socioeconomic status has been reported as one of the main factors of children malnutrition.…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that the prevalence of each type of malnutrition, in terms of wasting, stunting and underweight were 7.8, 12.4 and 10.5 percent, respectively. One reason for the rather high overall prevalence of all three indicators in this review is that the majority of studies were conducted in the cities or provinces in which socioeconomic status was middle or low and we know that health and economic differences across Iranian provinces are very wide (22,23). The household socioeconomic status has been reported as one of the main factors of children malnutrition.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, people living in areas with an abundant supply of healthcare services are more prone to utilise those services (supplierinduced demand); by contrast, zones where healthcare provision is low may be subject to so-called supplier-suppressed demand (Rice and Smith, 2001). Spatial inequalities in healthcare provision occur in both developing countries (Kumar, 2004;Abolhallaje et al, 2014) and industrialised ones (Houghton, 2005;Perez and Decoupigny, 2009). Limited geographical access not only reduces the availability of pharmaceuticals but also limits recommendations regarding their use (Norris et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet in the health district of SĂ©linguĂ©, close to the national capital, with moderate geographic access to health services, there are clear disparities within the district. As noted in existing studies, the unequal distribution of healthcare facilities according his geographical accessibility in West African regions is rarely discussed [23][24][25][26]. The internal disparities identi ed in this paper provide insight into why some women still experience poor maternal healthcare utilization and access, despite living in moderate geographic access regions of Mali.…”
Section: Discussionmentioning
confidence: 81%